A Socio-Pragmatic Study of Gender Differences in the Use of “Walak’ (Woe) and Its Variants in Spoken Jordanian Arabic - Rabab’ah, Ghaleb; Al-Yasin, Noor; Yagi , Sane (East European Journal of Psycholinguistics, 2022)
Using a mixed-method approach, this study examines the pragmatic functions of the discourse marker walak and its variants in Spoken Jordanian Arabic. It also explores the differences in the use of this discourse marker according to the speakers’ gender. The data was collected from a sample of 200 native speakers of Jordanian Arabic, using informal interviews and a validation questionnaire. The results showed that walak and its variants perform six language functions: warning, insulting, addressing/vocative, endearment, threatening, and denial. As far as gender differences are concerned, the findings indicated that there were statistically significant differences between males and females in the use of walak and its variants in favour of males. This indicates that males agreed more with the sentences expressing each pragmatic function in the validation questionnaire. The study concludes with some pedagogical implications for learners of Arabic as a second language, teachers and syllabus designers.